Avaliação da concordância no diagnóstico de arritmias entre médicos cardiologistas e não cardiologistas na emergência - Silva, Mirna Mendes da (2017)
Patients with arrhythmia may have severe clinical consequences, such as syncopes with falls to the ground and head trauma, decompensation of heart failure, acute pulmonary edema, myocardial ischemia, thromboembolic phenomena, and hemodynamic instability, which may lead to cardiopulmonary arrest and death. The correct diagnosis of arrhythmias by using the electrocardiogram (ECG) is fundamental so that the patient can receive the appropriate treatment. The correct interpretation of an ECG requires knowledge, skill and experience by the person who is analyzing the exam. Due to the clinical importance of the arrhythmias, it was decided to investigate if they are being recognized by the doctors who provide the initial care to patients who present this illness. Objective: To evaluate the diagnosis of arrhythmias (tachyarrhythmias and bradyarrhythmias) in emergency care units of Uberlândia / Minas Gerais, by comparing the analyses of electrocardiographic reports between cardiologists and emergency physicians. To evaluate the intraobserver agreement in the diagnosis of tachyarrhythmias and bradyarrhythmias in each one of the groups. Methods: Two groups of physicians who work in emergency departments in Uberlândia-MG were compared, with 17 participants in each one of them: cardiologists and emergency physicians, in two different moments, with an interval of three months. They were tested using a set of 15 ECGs -9 tachyarrhythmias and 6 bradyarrhythmias. They interpreted the ECGs and were scored on the number of correct diagnosis. Each ECG interpretation was defined as correct when compatible with the previous and concordant interpretation of three electrophysiologists, which was considered the gold standard diagnosis. Electrocardiograms´ correct diagnosis were assessed in both groups. Intraobserver agreement was analyzed in each one of the groups. Results: cardiologists had higher ratio of correct diagnosis of all arrhythmias in both phases (77,6% in phase 1, p=0,002; and 75,4% in phase 2, p<0,001). Cardiologists also had higher mean proportion of correct diagnosis for the two types of arrhythmias (tachyarrhythmias and bradyarrhythmias), in both phases (phase 1: 86,1% of tachyarrhythmias, p=0,005; 69,8% of bradyarrhythmias, p=0,006; phase 2: 81,9% of tachyarrhythmias, p=0,003; 65,6% of bradyarrhythmias, p<0,001). When assessing whether the type of ECG (tachyarrhythmia or bradyarrhythmia) could influence the physician's outcome (misdiagnosis or correct diagnosis), it was verified that tachyarrhythmia can be considered a risk factor for correctly answering. In phase 1 there was a decrease in the bradyarrhythmias’ correct diagnosis rate when compared to tachyarrhythmias’ by approximately 64% in the emergency physician group (OR = 0.357, CI [0.21-0.61]) and 63% in the cardiologists group (OR = 0.373, CI [ 0.20-0.71]). In phase 2 there was a decrease in the bradyarrhythmias’ correct diagnosis proportion by approximately 74% when compared to tachyarrhythmia’s in the emergency physician group (OR = 0.265; CI [0.15-0.46]) and round to 58% in the cardiologists group (OR = 0.421; CI [0.23-0.76]). Intraobserver agreement was moderate among subjects in the emergency physician group (general Kappa = 0.56) and fair in the cardiologists group (general kappa = 0.36). Conclusion: Cardiologists group had higher ratio of correct diagnosis not only of the arrhythmias in general, but also of tachyarrhythmias and bradyarrhythmias, in both phases. Tachyarrhythmias increased the physician' s chance to achieve the correct diagnosis. However, none of the groups showed strong intraobserver agreement.